The Origin and Occurrence of Natural Hydrogen - Wang, Lu; Jin, Zhijun; Chen, Xiao; Su, Yutong; Huang, Xiaowei (Energies (Basel), 2023)
Hydrogen is an attractive, clean, sustainable energy source primarily produced via industry. At present, most reviews on hydrogen mainly focus on the preparation and storage of hydrogen, while the development and utilization of natural hydrogen will greatly reduce its cost. Natural hydrogen has been discovered in many geological environments. Therefore, based on extensive literature research, in this study, the distribution and sources of natural hydrogen were systematically sorted, and the identification method and occurrence state of natural hydrogen were examined and summarized. The results of this research show that hydrogen has been discovered in oceanic spreading centers, transform faults, passive margins, convergent margins, and intraplate settings. The primary sources of the hydrogen include alterations in Fe(II)-containing rocks, the radiolysis of water, degassed magma, and the reaction of water- and silica-containing rocks during the mechanical fracturing. Hydrogen can appear in free gas, it can be adsorbed and trapped in inclusions. Currently, natural hydrogen exploration is in its infancy. This systematic review helps to understand the origin, distribution, and occurrence pattern of natural hydrogen. In addition, it facilitates the exploration and development of natural hydrogen deposits, thus enabling the production of low-cost hydrogen.